1997
DOI: 10.1021/ja9635239
|View full text |Cite
|
Sign up to set email alerts
|

Extended X-ray Absorption Fine Structure Analysis of Coenzyme B12 Bound to Methylmalonyl-Coenzyme A Mutase Using Global Mapping Techniques

Abstract: The two available crystallographic structures of cobalamin dependent enzymes, the 27 kDa fragment of the methylcobalamin-dependent enzyme, methionine synthase, from Escherichia coli [Drennan, C. L. et al. Science 1994, 266, 1669] and the 5‘-deoxyadenosylcobalamin-dependent enzyme methylmalonyl-coenzyme A mutase from Propionibacterium shermanii [Mancia, F. et al. Structure 1996, 4, 339], show striking similarities despite the differences in reaction mechanism. In particular, the 5,6-dimethylbenzimidazole group … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

5
49
1

Year Published

1999
1999
2004
2004

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 43 publications
(55 citation statements)
references
References 30 publications
(60 reference statements)
5
49
1
Order By: Relevance
“…[9Ϫ11,19,20] Comparison with those previously determined by EXAFS may be useful in order to establish the reliability of bond lengths determined solely by using the first-shell Fourier filter analysis of EXAFS data. [6,25] In particular, such a comparison is important in view of the recent controversial EX- [26,27] In molecular biology, EXAFS is an ideal complement to biocrystallography in establishing the coordination distances in metalloenzyme and, under favorable circumstances, it can give coordination distances with an accuracy of 0.01 Å . [28] However, the analysis generally furnishes several solutions, [26] often difficult to interpret without comparison with accurate X-ray structural data, which often cannot be obtained for metalloproteins.…”
Section: Comparison Of X-ray (Xrd) and Exafs Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…[9Ϫ11,19,20] Comparison with those previously determined by EXAFS may be useful in order to establish the reliability of bond lengths determined solely by using the first-shell Fourier filter analysis of EXAFS data. [6,25] In particular, such a comparison is important in view of the recent controversial EX- [26,27] In molecular biology, EXAFS is an ideal complement to biocrystallography in establishing the coordination distances in metalloenzyme and, under favorable circumstances, it can give coordination distances with an accuracy of 0.01 Å . [28] However, the analysis generally furnishes several solutions, [26] often difficult to interpret without comparison with accurate X-ray structural data, which often cannot be obtained for metalloproteins.…”
Section: Comparison Of X-ray (Xrd) and Exafs Resultsmentioning
confidence: 99%
“…Such a large discrepancy has been ascribed to the presence of the four equatorial nitrogen atoms, which limits the accuracy of the axial distances because their contribution to the EX-AFS spectrum interferes with that of the axial ligands. [27,29] The treatment of EXAFS data with the global mapping technique [26] has solved such a discrepancy in the case of (H 2 O)Cbl ϩ , although it has been pointed out that multiple solutions are generally possible. [27,29] Thus, for (H 2 O)Cbl ϩ , an alternative solution gave CoϪN and CoϪO distances in agreement with the crystallographic results (Table 4).…”
Section: Comparison Of X-ray (Xrd) and Exafs Resultsmentioning
confidence: 99%
“…Model studies have indicated that a weaker nitrogen donor ligand decreases the dissociation energy of the C-Co bond (33)(34)(35). Interest in this second hypothesis has been stimulated by extended x-ray absorption fine structure spectroscopy and x-ray crystallography studies on MMCoA mutase, which indicate displacement of the DMB lower axial ligand of 1 by a protein histidine in cob(II)alamin-bound MMCoA mutase, with a long Co-N bond (3,4,36). EPR studies on other AdoCbl-requiring carbon skeleton mutases reveal that these class I enzymes also utilize a histidine as their axial ligand (1,6) as do most of the cobalamin-dependent methyltransferases thus far examined (37)(38)(39).…”
Section: Discussionmentioning
confidence: 99%
“…In the two mutase structures (MCM, Glm), presumably a mixture of corrinoid cofactors with different oxidation states was present [26]. The length of this bond was also studied by X-ray absorption spectroscopy, which yielded an indication for bond elongation for MCM [37] and a more or less normal bond length for Glm [38]. However, recently we were able to show that under the conditions of a high-brilliance X-ray beam, photoreduction of the cofactor may occur, which would then suggest that at least some of the crystallographically observed bond elongation is in fact an artifact of the experimental technique [39].…”
mentioning
confidence: 99%